Implementation of Islamic Community Development in The Charter of Medina - Ghozali, Abdul Malik (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze the points of the Medina Charter as an implementation of the development of Medina society during the time of the Prophet Muhammad's preaching. Medina society was in reality a heterogeneous society consisting of various tribes and religions. Interactions between tribes and religions were often marked by friction and conflict that consumed time, energy, wealth, and lives. This raises the question of how the Medina Charter implemented the values of the Prophet's preaching regarding justice, equality, and freedom as the basis for community development. This research is a qualitative descriptive study in the form of a literature review using content analysis of the points of the Medina Charter with a takhrij approach, a study of sanad and hadith texts, history, and fiqhul hadith. The results of the study conclude that the points of the Medina Charter are a form of implementation of the development of a pluralistic Medina society. The Medina society became a role model for the application of a civilized, just, and equal society after the implementation of the points of the Medina Charter in their lives.